ARE EARTHQUAKES AN INSTANCE OF FLICKER NOISE? - Berdyyev A.A.; Mukhamedov V.A. (My University, 1987)
A comparsion is made of the physical patterns identified in the experimental study of the dynamic properties of rocks in three different types of research: derivation of frequency plots in the analysis of regional seismicity, investigation of inelastic properties with reference to absorption of seismic waves, and unsteady-state creep of rocks. The similarity in the power spectra of stress fluctuations in these three different processes indicates that they may belong to the same more general class of phenomena, so-called 'flicker noise,' in disordered structures. Based on experimental evidence, the pattern of intensified static and dynamic noise directly precedes the moment of loss of stability, i.e., the intensified noise is a short-range precursor of earthquakes.